Literature, Religion, and Science: A Personal and Professional Trajectory - Schaible, Robert (Zygon, 1997)
By tracing the trajectory of his own personal and professional life, the author provides a perspective on how intellectual and religious or spiritual growth, while often seemingly at odds with each other, can nonetheless advance in a mutually enhancing manner. The historical conflict between literature and science is briefly outlined as a parallel to that between religion and science, and the importance of metaphor as a common element in all three fields is explored. Emphasis is placed on metaphor as a means of challenging absolutism, encouraging humility, and promoting a sense of wonder about the universe.